Penerapan Kurikulum Pendidikan Agama Kristen Dalam Membangun Kerohanian Remaja Di GPIN Bukit Asam, Tanjung Enim (INSTITUTIO : Jurnal Pendidikan Agama Kristen, 2024)
Building the spirituality of adolescents is a crucial task, especially in the face of the influence of the times, which has significantly impacted the decline of adolescent spirituality today. The role of the Church, in this case, GPIN Bukit Asam, can serve as a platform to implement the Christian Religious Education curriculum as an effort to build the spiritual life of adolescents. This study aims to examine the implementation of the Christian Religious Education (CRE) curriculum in building adolescent spirituality at GPIN Bukit Asam. In the context of globalization and modernization, spirituality has become an important aspect that needs attention in the growth of adolescent faith. This research uses a qualitative method with a literature study approach. The results indicate that the effective implementation of the CRE curriculum can improve adolescents' understanding of Christian values and strengthen their faith. Furthermore, the involvement of teachers and the school environment also plays a significant role in building adolescent spirituality.